Word wall media in teaching vocabulary to junior secondary school students: teacher’s practices, benefits, and challenges - Syamsul Huda; Windhariyati Dyah Kusumawanti (Erudita: Journal of English Language Teaching, 2024)
This research aims to showcase teacher’s practices, benefits, and challenges of applying word wall media in teaching vocabulary to junior secondary school students. Designed with the qualitative case study, an EFL teacher of an Islamic junior high school in Banyumas, Central Java, Indonesia, volunteered to participate. Data were collected through interviews, classroom observation, and documentation. This study employed an interactive model of data analysis. Study findings demonstrated that there were five stages in implementing word wall media, i.e. planning vocabulary, designing the word wall, placing the word wall, using the word wall, and practicing advanced use. Another finding also illustrated the benefits of using word wall media in teaching vocabulary. The word wall media could help junior secondary school students familiarize themselves with vocabulary, motivate them to elevate vocabulary acquisition, foster them in reading and writing, and encourage them to communicate in English. The application of word wall also benefited the EFL teacher in designing vocabulary teaching and learning that suited the students’ language target and managed the class in a more engaged way. Further, the teacher encountered some challenges in applying the word wall media, including student teamwork, application consistency, and the learning media’s practicality.